2010
DOI: 10.1007/bf03391607
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and Advancing the Health of Older Populations in sub-Saharan Africa: Policy Perspectives and Evidence Needs

Abstract: Background: Debate on policy challenges associated with the health of older populations in sub-Saharan Africa (SSA) has intensified in recent years, centering on a concern about older persons' vulnerability to ill-health and their exclusion from health services. Despite international policy calls and formal expressions of commitment on the part of SSA governments, comprehensive policy action has remained scant. The impasse reflects a lack of political will and an uncertainty about required policy approaches, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
61
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 63 publications
3
61
0
1
Order By: Relevance
“…Physical and financial constraints impede timely utilization of available health care services. Impeded access can lead to underutilization of primary and preventive health care services which in turn may result in unnecessary hospitalizations, increased morbidity and higher costs of the health care system than necessary [10].…”
Section: Introductionmentioning
confidence: 99%
“…Physical and financial constraints impede timely utilization of available health care services. Impeded access can lead to underutilization of primary and preventive health care services which in turn may result in unnecessary hospitalizations, increased morbidity and higher costs of the health care system than necessary [10].…”
Section: Introductionmentioning
confidence: 99%
“…Many older women report lower health status, higher disability, and poorer quality of life compared to their male counterparts [17]. This situation is not peculiar to South Africa; Aboderin [18], also reported that access to healthcare and essential medicines for NCDs is a challenge for the elderly in Africa. Such access to healthcare may be limited for older women in light of their multi-tasking roles and perhaps, cultural restrictions.…”
Section: Introductionmentioning
confidence: 99%
“…Such access to healthcare may be limited for older women in light of their multi-tasking roles and perhaps, cultural restrictions. Lack of income and limited transportation to hospitals within the continent are additional barriers which may be faced by elderly people with NCDs in their quest for proper healthcare [18, 19]. We hypothesize that these challenges may prompt older women in a South African peri-urban/township area to seek readily accessible treatment options to take care of their health conditions.…”
Section: Introductionmentioning
confidence: 99%
“…It addresses the multilevel approaches needed to support longer lives that are healthy and active: from life course approaches to prevention to redesign of our built environment and our institutions to support activity and independence, to adapting our health systems to provide prevention and care that better matches the health needs of people with multimorbidity -and likely at lower cost. The paper by Isabella Aboderin appropriately summarizes the policy challenges faced by sub-Saharan Africa, 13 which has both the fastest growing elderly population of any world region and the substantial persistence of classical tropical diseases, in addition to an increasing superimposition of chronic non-communicable diseases. The case report by Alban Ylli from Albania describes the situation of an already-aged society in which substantial unmet needs exist for older adults.…”
mentioning
confidence: 99%